Interleukin 34, from pathogenesis to clinical applications. (November 2017) - Baghdadi, Muhammad; Endo, Hiraku; Tanaka, Yoshino; Wada, Haruka; Seino, Ken-ichiro
Highlights: IL-34 is expressed specifically in the skin and CNS under physiological conditions. IL-34 can be induced under various pathological conditions. IL-34 may serve as a diagnostic tool and novel biomarker of disease. IL-34 may serve as a promising therapeutic target in medicine. Abstract: Interleukin-34 (IL-34) is a hematopoietic cytokine that was described for the first time in 2008 as a second ligand of CSF1R in addition to M-CSF. IL-34 and M-CSF share no sequence homology, but have similar functions, affecting the biology of myeloid cell lineage. In contrast to M-CSF, IL-34 shows unique signaling and expression patterns. Physiologically, IL-34 expression is restricted to epidermis and CNS, acting as a regulator of Langerhans cells and microglia, respectively. However, IL-34 expression can be induced and regulated by NF-κB under pathological conditions. Importantly, growing evidence indicates a correlation between IL-34 and disease severity, chronicity and progression. In addition to its promising roles as a novel diagnostic and prognostic biomarker of disease, IL-34 may also serve as a powerful target for therapeutic intervention. Here, we review the current knowledge regarding the emerging roles of IL-34 in disease, and focus on the clinical applications of IL-34 in medicine.